Bangladesh : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Waiver of Nonobservance of a Performance Criterion-Staff Report, Staff Statements and Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bangladesh. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
Fiscal performance has been broadly in line with program targets. As a result, the current account deficit has narrowed, reserves have increased significantly, and headline inflation is under control. However, implementation of structural benchmarks has lagged, necessitating sharper focus and greater ownership by the authorities. The global economic slowdown coupled with election-year uncertainty in Bangladesh poses the most immediate challenge to policymakers. The balance of risks is to the downside in the near term, potentially putting pressure on growth and inflation and undermining financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet